Harnessing Bourdieu's social theory to understand the deteriorating doctor-patient-nurse relationship in West Bengal government hospitals - Sarkar, Tannistha (Frontiers in Sociology, 2022)
Communication patterns between doctors, nurses and patients determine both the efficiency of healthcare delivery, and the job satisfaction of healthcare workers. Job satisfaction is important to ensure retention of the doctor and nurse populations. Incidents of assault against physicians and nurses from relatives and family members of patients have become frequent both in the pre-pandemic and COVID-19 eras. Along with appreciation for frontline healthcare workers serving during the pandemic, there is physical violence directed at them for failing to salvage infected patients. Using Bourdieu's concepts of social space, forms of capital, and habitus this paper endeavors to theorize some of the interaction patterns observed in doctor-patient, nurse-patient, and doctor-nurse encounters that contribute to the waning of the relationship between healthcare workers and wider society as observed in West Bengal, India. Primary empirical data was collected through in-person, in-depth semi-structured interviews with both open and closed-ended questions conducted throughout 2018 across 5 government hospitals in Kolkata (major metropolitan center) and 1 hospital in a suburban area with population 100,000. The respondents consisted of 51 nurses (100% women), 20 doctors (5% women), and 33 patients (33.3% women) recruited using purposive and snowball sampling. Social space analysis indicated that the cumulative patient social capital is comparable to that of the doctors, despite the doctor's higher levels of cultural and economic capital because of the high patient to doctor ratio. The patient population can thus concentrate and delegate their social capital to select agents leading to violence against healthcare workers. Through this analysis, two doctors' habitus were postulated, along with a nurse and a patient habitus. The first doctor habitus is structured by the idealized status of doctors and the second habitus is structured by their resource-limited working conditions. The nurse habitus is structured by the desire for economic empowerment along with dutifully providing care as instructed. The patient habitus is structured by the need to balance healthcare expenditures with their limited financial means. This paper establishes how the habitus of the agents and the politics of healthcare interact to exacerbate extant tensions between healthcare workers and the population they care for.